Daily Oscillation of the Excitation-Inhibition Balance in Visual Cortical Circuits - Bridi, Michelle C.D.; Zong, Fang-Jiao; Min, Xia; Luo, Nancy; Tran, Trinh; Qiu, Jiaqian; Severin, Daniel; Zhang, Xue-Ting; Wang, Guanglin; Zhu, Zheng-Jiang; He, Kai-Wen; Kirkwood, Alfredo (Neuron (Cambridge, Mass.), 2020)
A balance between synaptic excitation and inhibition (E/I balance) maintained within a narrow window is widely regarded to be crucial for cortical processing. In line with this idea, the E/I balance is reportedly comparable across neighboring neurons, behavioral states, and developmental stages and altered in many neurological disorders. Motivated by these ideas, we examined whether synaptic inhibition changes over the 24-h day to compensate for the well-documented sleep-dependent changes in synaptic excitation. We found that, in pyramidal cells of visual and prefrontal cortices and hippocampal CA1, synaptic inhibition also changes over the 24-h light/dark cycle but, surprisingly, in the opposite direction of synaptic excitation. Inhibition is upregulated in the visual cortex during the light phase in a sleep-dependent manner. In the visual cortex, these changes in the E/I balance occurred in feedback, but not feedforward, circuits. These observations open new and interesting questions on the function and regulation of the E/I balance. •The excitation/inhibition (E/I) ratio is dynamic across the 24-h day•Fluctuations in the E/I ratio depend on sleep/wake history•E/I ratio changes are circuit specific, not uniform across all synapses Bridi et al. investigate whether inhibition tracks known changes in excitation over the 24-h day to maintain a stable excitation/inhibition ratio. Surprisingly, the excitation/inhibition ratio is dynamic over the day in feedback, but not feedforward, visual cortical circuits.